Atrazine interaction with tropical humic substances by Enzyme Linked Immunosorbent Assay - Toscano, I; Gascon, J.; Marco, M. P.; Rocha, Julio Cesar [UNESP]; Barcelo, D. (E D P Sciences, 1998)
Enzyme-Linked Immunosorbent Assay (ELISA) has been evaluated by analyzing rich-humic water samples from tropical rivers. The samples were spiked with atrazine at ppb level Different pHs (4 to 9) and humic concentrations (2.5 to 40 mg L-1) were investigated. The assay performance showed a strong dependence on the pH values and amount of humic matter at low atrazine concentration. From all the conditions studied the low pH (pH 4) and high humic substances concentrations (40 mg L-1) showed the greatest influence. The IC50 value to control sample (no humic) diminished from 0.28 nmol L-1 to 0.64 nmol L-1 to humic acid solution. This effect is specially noted for the humic acid fractions, since fulvic acid fractions showed no significant change on the immunoassay results. Additionally, it has been demonstrated that at basic pH the matrix effect produced by the natural Brazilian water sample containing humic substances even at 40 mg L-1 disappears. Therefore, the ELISA method used to determine atrazine, can be employed to determine this pesticide in water samples containing humic substances without prior preparation.
Keywords: atrazine; aquatic humic substances; immunoassays